2012
DOI: 10.1002/bdm.1751
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of an Abbreviated Numeracy Scale: A Rasch Analysis Approach

Abstract: Research has demonstrated that individual differences in numeracy may have important consequences for decision making. In the present paper, we develop a shorter, psychometrically improved measure of numeracy-the ability to understand, manipulate, and use numerical information, including probabilities. Across two large independent samples that varied widely in age and educational level, participants completed 18 items from existing numeracy measures. In Study 1, we conducted a Rasch analysis on the item pool a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
384
3
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 339 publications
(437 citation statements)
references
References 55 publications
(105 reference statements)
26
384
3
8
Order By: Relevance
“…Research has shown that people who perform well on the CRT tend to perform well on numeracy tests. Specifically, significant, moderate correlations have been found between performance on the CRT and mathematical ability, as indexed by numeracy, math achievement or math skills (r = 0.25, G omez-Chac on, Garc ıa-Madruga, Vila, Elos ua, & Rodr ıguez, 2014; r = 0.31, Cokely & Kelley, 2009;Primi et al, 2016; rs ranging from 0.37 to 0.51, Liberali, Reyna, Furlan, Stein, & Pardo, 2012;r = 0.43, Campitelli & Gerrans, 2014;Weller et al, 2013; r = 0.44 with numeracy and r = 0.61 with calculation, Sinayev & Peters, 2015; rs ranging from 0.29 to 0.45, Morsanyi et al, 2014;r = 0.53, Finucane & Gullion, 2010; r = 0.58, Thomson & Oppenheimer, 2016).…”
Section: Thinking and Reasoningmentioning
confidence: 99%
“…Research has shown that people who perform well on the CRT tend to perform well on numeracy tests. Specifically, significant, moderate correlations have been found between performance on the CRT and mathematical ability, as indexed by numeracy, math achievement or math skills (r = 0.25, G omez-Chac on, Garc ıa-Madruga, Vila, Elos ua, & Rodr ıguez, 2014; r = 0.31, Cokely & Kelley, 2009;Primi et al, 2016; rs ranging from 0.37 to 0.51, Liberali, Reyna, Furlan, Stein, & Pardo, 2012;r = 0.43, Campitelli & Gerrans, 2014;Weller et al, 2013; r = 0.44 with numeracy and r = 0.61 with calculation, Sinayev & Peters, 2015; rs ranging from 0.29 to 0.45, Morsanyi et al, 2014;r = 0.53, Finucane & Gullion, 2010; r = 0.58, Thomson & Oppenheimer, 2016).…”
Section: Thinking and Reasoningmentioning
confidence: 99%
“…To assess numeracy and analytical thinking, we include five numeracy questions and three cognitive reflection task (CRT) questions for a subset of our total survey population 2 (Weller et al 2012, Frederick 2005.…”
Section: Study Design: Attribute Selection Model Specification and mentioning
confidence: 99%
“…Indeed, multiple researchers have worked to create short questionnaires that capture the distribution of this skill in a population (e.g., Cokely, Galesic, Schulz, Ghazal, & Garcia-Retamero, 2012;Lipkus, Samsa, & Rimer, 2001;Weller et al, 2013). However, metrics of individual differences in ANS acuity are less well investigated.…”
Section: Motivation Of the Present Studymentioning
confidence: 99%